Potential Determinants of Profits and Market Efficiency of Potato Market Chains in Uganda - Kyomugisha, Harriet; Mugisha, Johnny; Sebatta, Christopher (Journal of Agribusiness in Developing and Emerging Economies, 2017)
The study aimed at understanding the level of inefficiencies in the potato market chain. Farmers sell potato to traders but continue to complain of limited market access and low profits. The purpose of this paper is to determine market efficiency and profits of the potato market chain, and factors that influence the profits.The study focussed on potato farmers, traders and small-scale processors. It was conducted in Kabale and Mbale districts being the major potato producing areas in Uganda, and Kampala being a major potato market. Data were collected from 180 farmers, 60 traders and 32 small-scale processors. Descriptive and regression methods were used to analyse the data.There were three major potato market chains and all were profitable and efficient. The farmer-buyer node was the most efficient (efficiencies of 128-159 per cent). The trader node efficiency ranged between 56 and 81 per cent. Sex of chain actor, group marketing, contract duration and distance to market were among the factors that affected profits.Processors considered were those operating on very small scale, hence results do not apply to large-scale processing. Consumers were not included but the data and results are adequate for the study objective.This paper provides empirical information that serves as a basis to adopt market options for increased benefits to various chain actors.
Keywords: Efficiency, market chains, potato, profits, Uganda